Analysis of the Effectiveness of E-Office Application Users of the Human Resources Bureau of the University of North Sumatra - Mehta Gafari Lubis; Nazaruddin; Muhammad Anggia Muchtar (East Asian Journal of Multidisciplinary Research, 2023)
Digitalization has the potential to improve services and connect people to numerous types of information. The University of North Sumatra (USU) in Indonesia also uses digitization through the Human Resources Bureau (HR) with the E-Office application. The purpose of this study is to examine the effectiveness and user satisfaction of the E-Office program in order to increase employee performance by examining the relationship between the two using the Technology Acceptance Model (TAM) theory. This study employs quantitative research techniques. This study collects data through non-probability sampling from primary and secondary sources. This study's data analysis methodologies include descriptive statistical analysis, partial least squares (PLS) statistics, hypothesis testing, and significance testing. The findings revealed that employee knowledge of how to use E-Office software had a substantial impact on enhancing operational efficiency.